Zero Fluoroscopy Transcatheter Device Closure in Subaortic Ventricular Septal Defect - Marco Wirawan Hadi; Tahari Bargas Prakoso; Rille Puspitoadhi Harjoko; Sefri Noventi Sofia (RSUP Dr. Kariadi, 2025)
Background: For the last decade, transcatheter closure of ventricular septal defect (VSD) has been the treatment of choice, using fluoroscopy as a guide. However, the risk of radiation and/or contrast agent exposure has been an issue, especially in young patients. We would like to highlight the first case of zero fluoroscopy transcatheter VSD closure in Central Java. Case Illustration: A 27-year-old female was referred to outpatient department due to worsening shortness of breath in the last 3 months before admission. She had a history of recurrent respiratory tract infections, feeding difficulty, and failure to thrive. Her vital signs were stable, 99% oxygen saturation, and grade 3/6 pansystolic murmur in the lower left sternal border. Transoesophageal echocardiography showed 3 mm subaortic VSD, left to right shunt. Transcatheter VSD closure was successfully done using Konar-MF™ VSD Occluder No. 8/6 mm retrograde approach without fluoroscopy. Conclusion: The first zero fluoroscopy transcatheter device closure in Central Java has been successfully done in a 27-year-old female with subaortic VSD. Zero fluoroscopy transcatheter VSD closure is a feasible, safe, and effective procedure.